2016
DOI: 10.1155/2016/9579868
|View full text |Cite
|
Sign up to set email alerts
|

The Janus‐Faced Role of Antioxidants in Cancer Cachexia: New Insights on the Established Concepts

Abstract: Chronic inflammation and excessive loss of skeletal muscle usually occur during cancer cachexia, leading to functional impairment and delaying the cure of cancer. The release of cytokines by tumor promotes the formation of reactive oxygen species (ROS), which in turn regulate catabolic pathways involved in muscle atrophy. ROS also exert a dual role within tumor itself, as they can either promote proliferation and vascularization or induce senescence and apoptosis. Accordingly, previous studies that used antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 164 publications
(219 reference statements)
0
29
0
Order By: Relevance
“…iNOS has been proven to be an important mediator in TNF α -induced cachectic muscle loss and in age-related muscle wasting (sarcopenia) [ 21 ]. Under pathological conditions, the activation of iNOS promotes muscle atrophy [ 62 ]. NO may exert both protective and pathological effects during muscle wasting, depending on quantitative effects as well as on the spatial arrangement of NOS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS has been proven to be an important mediator in TNF α -induced cachectic muscle loss and in age-related muscle wasting (sarcopenia) [ 21 ]. Under pathological conditions, the activation of iNOS promotes muscle atrophy [ 62 ]. NO may exert both protective and pathological effects during muscle wasting, depending on quantitative effects as well as on the spatial arrangement of NOS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cachexia appears in nearly 50% of patients with advanced stage of cancer and leads to progressive functional impairment, decreased quality of life with respiratory complications, and death can occur following the loss of 75% of skeletal muscle mass. [4][5][6] We have recently found that three genes encoding for proteins of the C-X-C motif chemokine receptor 4 pathway are down-regulated in the atrophying gastrocnemius of Yoshida hepatoma-bearing rats: stromal cell-derived factor 1, adenylate cyclase 7, and p21 protein-activated kinase 1 (Pak1). 7,8 Paks are Ser/Thr kinases acting as downstream effectors of the p21 small GTPases Rac1 and Cdc42.…”
Section: Introductionmentioning
confidence: 99%
“…General antioxidants have been the subject of intense research for cancer prevention and treatment. Because these molecules indistinctively target different cell types (including tumor-resident non-malignant host cells, some of which promote and some of which repress tumor progression), because they are not selective for a given ROS produced at a precise subcellular location and because they can interfere with anticancer therapy, general antioxidants have unpredictable effects on cancer progression ( Bonner and Arbiser, 2014 ; Milkovic et al, 2014 ; Ozben, 2015 ; Assi and Rebillard, 2016 ; Russo et al, 2017 ). For examples, chronic vitamin E supplementation was found to significantly increase prostate cancer incidence in humans ( Klein et al, 2011 ), vitamin C has no significant anticancer effects even when administered intravenously at high dose ( Jacobs et al, 2015 ), and N -acetylcysteine can promote metastasis by improving the resistance of cancer cells to oxidative stress during cell detachment and in the blood stream ( Le Gal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%